A semi‐analytical formula for calculating the notch stress field of cruciform welded joint under bending loading. Issue 11 (9th August 2020) - Shen, Wei; Qiu, Yu; Xu, Lin; Liu, Enqian
Abstract: A fine finite element model should be established in fatigue assessment of cruciform welded specimens in notch stress method, and there is no analytical or empirical notch stress formula suitable for engineering application. Based on linear elastic fracture mechanics (LEFM) and singular strength theory, this paper put forward a simple semi‐analytical formula of notch stress for commonly used cruciform joints. Considering the influence of incision types and different opening angles, the proposed formula is further extended to U‐shaped notch and other common opening angles. After a series of verification, it is found that the proposed semi‐analytical stress formula based on singular strength values can simply and accurately predict the notch stress under bending loading, which provides a simple assessment approach for fatigue assessment of cruciform welded joints in engineering.